1988
DOI: 10.1002/ar.1092200404
|View full text |Cite
|
Sign up to set email alerts
|

Regional differentiation in the stomach of the green anole

Abstract: The stomach of Anolis carolinensis (Reptilia: Iguanidae) has four histologically and histochemically distinct regions. The gastroesophageal junction has an acidic surface mucin and no glands. The cardia has an acidic surface mucin and mucous glands. This acidic mucin appears to contain neither sulfates nor sialic acid. The fundus has a neutral surface mucin and mucoserous glands. The pylorus has a neutral surface mucin and mucous glands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…A similar study conducted on others species of lower vertebrates, the skink E. latiscutatus and snake E. climacophora (Suganuma et al 1981), showed that the production of acidic mucins predominates in the oesophageal tract. Mucous cells of the stomach of T. carnifex mainly produce neutral glycoproteins as seen in the green toad B. viridis (Liquori et al 2002) and in some reptiles (Lehman and Smith 1975;Ferri and Liquori 1992). In Rana a. aurora (Ferri et al 2001), some species of reptiles (Suganuma et al 1981), many mammals (Spicer and Sun 1967) and some species of fish (Domeneghini et al 2005) these cells secrete neutral and acid mucins.…”
Section: Discussionmentioning
confidence: 96%
“…A similar study conducted on others species of lower vertebrates, the skink E. latiscutatus and snake E. climacophora (Suganuma et al 1981), showed that the production of acidic mucins predominates in the oesophageal tract. Mucous cells of the stomach of T. carnifex mainly produce neutral glycoproteins as seen in the green toad B. viridis (Liquori et al 2002) and in some reptiles (Lehman and Smith 1975;Ferri and Liquori 1992). In Rana a. aurora (Ferri et al 2001), some species of reptiles (Suganuma et al 1981), many mammals (Spicer and Sun 1967) and some species of fish (Domeneghini et al 2005) these cells secrete neutral and acid mucins.…”
Section: Discussionmentioning
confidence: 96%
“…The cardiac, fundic, and necks of the pyloric glands did not stain, but the bases of the pyloric glands did stain with zirconyl hematoxylin. The forestomach mucin of the green anole is probably a uronic acid (Lehman and Smith 1988).…”
Section: Resultsmentioning
confidence: 99%
“…guishing one region of the digestive tract from another (Lehman and Smith 1988). The difference between neutral and acidic mucins can also assist in distinguishing normal from malignant prostate epithelium (Hukill and Vidone 1967, Rnder and McMahon 1990, Bancroft and Stevens 1996.…”
mentioning
confidence: 97%
“…Similarly, a uniform distribution of the pepsinogen and the tubulo-vescicular system was observed also in the crested newt, Triturus carnifex (Liquori et al, 2005). Since an oral-aboral variation in those features of the oxynticopeptic cells related to gastric juice secretion is widespread in nonmammalian vertebrates (e.g., Wright et al, 1957;Giraud et al 1979;Lehman and Smith, 1988;Arena et al, 1990;Gabrowski et al 1995;Ferri et al 1999;Liquori et al 2000;Liquori et al, 2002), it could be inferred that the condition of both Triturus carnifex and T. scripta is primitive and that the morphofunctional gradient along the fundus arose several times in the evolution of vertebrates. The pyloric glands of T. scripta differ from the fundic glands in lacking the lesser tubules with the oxynticopeptic cells.…”
Section: Discussionmentioning
confidence: 97%
“…The oxynticopeptic cells are clustered in the gastric g l a n d s o f t h e f u n d u s a n d p r o d u c e t h e t w o m a i n components of gastric juice, pepsinogen and hydrochloric acid. In some lizards and in the Greek tortoise, Testudo graeca, the amount and size of pepsinogen granules in the oxynticopeptic cells decreases from the oral to the aboral region of the fundus (e.g., Wright et al, 1957;Lehman and Smith, 1988;Arena et al, 1990;Ferri et al, 1999;Liquori et al, 2000). Accordingly, the development of the tubulo-vesicular system that in the oxynticopeptic cells is related to the HCl secretion increases from the oral to the aboral fundus (Ferri et al, 1999;Liquori et al, 2000).…”
Section: Lectin Histochemistrymentioning
confidence: 99%